The Role of Emotional Intelligence, Sales Strategies, Customer Trust, and Service Differences in Increasing Repurchase Intentions in Online Entrepreneurship in Indonesia - Souisa, Wendy; Lussy, Kalsum; Tetelepta, Maria Marlyn; Tutupoho, Fauzia (The Eastasouth Management and Business, 2025)
This study investigates the influence of emotional intelligence, sales strategies, customer trust, and service differences on repurchase intentions in the context of online entrepreneurship in Indonesia. With a quantitative approach, data were collected from 250 online consumers using a Likert scale (1–5) and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS 3). The results reveal that emotional intelligence and sales strategies significantly affect repurchase intentions both directly and indirectly through customer trust. Furthermore, service differences also show a strong direct relationship with repurchase intentions. Customer trust emerges as a vital mediating variable that enhances the impact of emotional and strategic efforts on customer loyalty. These findings highlight the importance of combining interpersonal competencies, marketing strategies, and value-added services to sustain customer retention in the Indonesian digital marketplace. The study offers practical insights for online entrepreneurs aiming to build long-term customer relationships and improve business sustainability.